Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Ketepatwaktuan Penyampaian Laporan Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Swenditayani, Ni Luh Mita; Padnyawati, Kadek Dewi; Erlina Wati, Ni Wayan Alit (Hita Akuntansi dan Keuangan, 2025)
Financial reports are a source of company financial information needed by investors, creditors, and users who need this information. The prompt submission of these reports plays a vital role in delivering pertinent information. Relevance of financial statements is contingent upon their timely delivery and the benefits they offer to users. This research seeks to assess how Financial reports are a source of company financial information needed by investors, creditors, and users who need this information. The prompt submission of these reports plays a vital role in delivering pertinent information. Relevance of financial statements is contingent upon their timely delivery and the benefits they offer to users. This research seeks to assess how Profitability, Leverage, and Company Size impact the punctuality of submitting financial statements among manufacturing firms listed on the Indonesia Stock Exchange between 2018 and 2021. The study's population consists of financial statements from manufacturing companies listeid on the Indonesia Stock Exchange (IDX) during the aforementioned priod. Purposive sampilng was used to sample a total of 209 businesses, and testing methods included logistic regression analysis. The findings of this study suggest that profitability influences the timely submission of financial reports in a favorable way. Leverage has no impact on how quickly financial reports must be submitted. A company's size has a beneficial impact on how quickly financial reports are submitted.